A comparative study on the dynamic heterogeneity of supercooled polymers under nanoconfinement. Issue 28 (9th July 2019) - Li, Shu-Jia; Qian, Hu-Jun; Lu, Zhong-Yuan
Abstract : Dynamic gradient and faster dynamics on average in polymer thin films are two leading factors, resulted from the nanoconfinement effect, have distinct influences on spatial and temporal parts of the dynamic heterogeneity in the system. Abstract : Dynamic heterogeneity (DH) is a universal property of glass transition phenomena. In this work, we perform a comparative analysis of DH for pure polymer and polymer/nanoparticle composite systems in both film and bulk states via molecular dynamics simulations. We find that the dynamic gradient and the faster average dynamics due to the presence of a free surface are two leading factors, resulting from a nanoconfinement effect, which influence different parts of DH in a film system. The dynamic gradient results from differences in dynamics at different distances from the mobile surface, which induces a large deviation from the Gaussian distribution for the displacement distribution in the film. At the same time, the maximum string size which describes the region size for cooperative motion (dynamic correlation) can also be influenced by the dynamic gradient, although this influence is much weaker than that on the displacement distribution. On the other hand, reflecting temporal fluctuations of dynamics or temporal parts of DH, characteristic peak times of the non-Gaussian parameter and string size, and the ratio between persistent times and exchange times which describe the dynamic exchange properties, are mainly influenced by the faster dynamics on average. Our results demonstrate that measuring different properties (dynamic distribution, dynamic correlation or dynamic exchange) place an emphasis on distinct temporal and spatial parts of DH. It is necessary to use combinational measurements of these properties to give a complete picture of DH in nanoconfinement environments.